Factors influencing the disclosure of carbon emissions in indonesia - Mela, Nanda Fito; Putra, Adhitya Agri; Abdurrahman, Rezi (JIFA (Journal of Islamic Finance and Accounting), 2023)
As global attention on environmental sustainability intensifies, understanding the factors influencing corporate transparency in carbon emissions has become increasingly urgent. This analysis aimed to discover whether or not differences in business characteristics such as size, leverage, institutional ownership, foreign ownership, CEO narcissism, CEO tenure, family ownership, and gender parity on the board of directors were associated with changes in emissions. The population of companies involved in agriculture and mining listed on the Indonesia Stock Exchange from 2018 to 2020 makes up the study's population. We selected 177 firms for this study to participate in our sample. Multiple linear regressions were used as a method of analysis. This research found that the size and leverage of a firm are significant determinants of the amount of data accessible about that company's carbon impact. Disclosure of carbon emissions is unaffected by institutional ownership, foreign ownership, CEO narcissism, family ownership, or the presence of women on boards of directors. These findings suggest that policymakers and corporate stakeholders should focus on size and leverage as key factors for improving carbon disclosure practices, while other business characteristics may require additional scrutiny.